2001
DOI: 10.1038/35066553
|View full text |Cite
|
Sign up to set email alerts
|

Increases in greenhouse forcing inferred from the outgoing longwave radiation spectra of the Earth in 1970 and 1997

Abstract: The evolution of the Earth's climate has been extensively studied, and a strong link between increases in surface temperatures and greenhouse gases has been established. But this relationship is complicated by several feedback processes-most importantly the hydrological cycle-that are not well understood. Changes in the Earth's greenhouse effect can be detected from variations in the spectrum of outgoing longwave radiation, which is a measure of how the Earth cools to space and carries the imprint of the gases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 18 publications
6
109
0
5
Order By: Relevance
“…1b). Nonetheless, recognising that over a multi-decadal time gap certain forcing signatures should be imprinted in the OLR spectrum, Harries et al conducted a comparison of clear-sky observations from IRIS-D with those taken almost 30 years later from the Interferometric Monitor for Greenhouse Gases (IMG) [52]. Their findings, re-plotted here in Fig.…”
Section: A Topic Revisited: 1990s-early 2000smentioning
confidence: 95%
“…1b). Nonetheless, recognising that over a multi-decadal time gap certain forcing signatures should be imprinted in the OLR spectrum, Harries et al conducted a comparison of clear-sky observations from IRIS-D with those taken almost 30 years later from the Interferometric Monitor for Greenhouse Gases (IMG) [52]. Their findings, re-plotted here in Fig.…”
Section: A Topic Revisited: 1990s-early 2000smentioning
confidence: 95%
“…Harries et al (2001) demonstrated that nadir radiance measurements taken by the IRIS instrument in 1970 can be compared with that provided by IMG in 1997, to access the climate forcing due to the increase in greenhouse gases.…”
Section: Climate Gasesmentioning
confidence: 99%
“…To examine the increase in the greenhouse effect in recent years corresponding to the CO2 concentration increase in the atmosphere, Harries et al (2001), analyzed the difference between the spectra of outgoing longwave radiation (OLR) obtained in 1970 by the IRIS satellite and in 1997 by the IMG satellite of the Japanese Space Agency. The data utilized over a 26-year period showed a number of differences in the land-masked and cloud-cleared data, which the authors attributed to changes in atmospheric concentrations of CH4, CO2, O3, CFC-11 and CFC-12.…”
Section: The Verdict On the Effect Of Co2 On Climate Changementioning
confidence: 99%